Representasi Gender dalam Al-Qur'an: Tinjauan Kritis Terhadap Narasi Perempuan - Khairanis, Retisfa; Aldi, Muhammad (Institut Riset dan Publikasi Indonesia (IRPI), 2025)
This research aims to explore gender representations in the Qur'an with a focus on women's narratives. The background of this research is rooted in the need to understand how Islam's sacred texts portray the role and position of women, as well as the implications for gender thinking in Muslim societies. While there have been various studies on gender in the Qur'?n, there is still room for a more in-depth and critical analysis of narratives that are often overlooked. The aim of this research is to provide a critical review of women's narratives in the Qur'an, identify key themes, and analyze how interpretations of these texts influence gender understanding among Muslims. The scope of the study includes verses related to women, both in their historical context and their relevance in the modern era. The method used in this research is a literature review, which involves collecting and analyzing various literary sources, including classical and contemporary tafsir, academic articles, and feminist works. The results show that women's narratives in the Qur'an have a complexity that is often overlooked, with several verses affirming equality and respect for women. The research also identifies variations in interpretation that can strengthen or weaken women's gender position in society. The findings are expected to contribute to discussions on gender and Islam and encourage more inclusive interpretations. Keyword: Representation, Gender, Qur'an, Women Narratives